SOME REPRODUCTIVE BIOLOGY OF SKIPJACK TUNA (Katsuwonus pelamis LINNAEUS, 1758) IN TOLI-TOLI WATERS, CENTRAL SULAWESI - Umi Chodrijah; Thomas Hidayat; Karsono Wagiyo (Indonesian Fisheries Research Journal, 2020)
Skipjack tuna (Katsuwonus pelamis) was one of the export commodities, where the demand and exploitation tend to increase, so sustainable fisheries management is needed based on biological data. The objective of the research was to study the several aspects of biology including of length of weight relationship, sex ratio maturity stage, gonada somatic index (GSI), length at first capture, and length at first maturity. The research was conducted in February - December 2015 in Toli-toli, Central Sulawesi. The results showed that the skipjack tuna growth pattern was allometrically positive (b= 3,318 for male and b = 3.3049 for female), where growth weight was faster than the increased length. The length of the first time capture skipjack tuna of pole and line (43.49 cmFL) was bigger than length at first maturity (41,007 cmFL). It means the mostly skipjack tuna caught have already spawned. The spawning season occurred throughout the year with spawning peaks are in April and September, with fecundity ranging from 450,570 to 1,707,390 eggs.